Application of The Principle of Freedom of Contract In The Rusunawa Lease Agreement Between Residents Affected by Eviction of Jakarta (Case Study of Eviction Affected Residents Who Live In Rusunawa Rawa Bebek) - Marcella Azzahra; Ridha Wahyuni (Journal of Law, Politic and Humanities, 2024)
This study aims to evaluate the implementation of the principle of freedom of contract in lease agreements involving residents displaced by eviction and to outline the legal measures available to these residents to prevent future evictions. The research employs an Empirical Juridical method and an analytical descriptive approach, incorporating a case study approach. The findings reveal that, while the principle of freedom of contract underpins agreements, it is not evident in the case of residents evicted from the Ciliwung river area and relocated to the Rawa Bebek flats. These residents are compelled to use a lease agreement method that does not reflect the principle of freedom of contract, forcing them to accept the terms imposed. From the perspective of the evicted residents, the principle of freedom of contract is absent in the lease agreement process. To address this, residents can pursue non-litigation measures such as mediation and negotiation, as well as litigation through the courts.